Amide as Terminal Groups: Synthesis and Properties as New Tolane‐Type Liquid Crystals. Issue 7 (12th June 2015) - Zhang, Hong; Hong, Fengying; Zhu, Dezhao; Xia, Zhengce; Wu, Hongxiang; Wang, Hui; Zeng, Zhuo
Abstract A series of novel tolane‐type liquid crystals with amide group as terminal group have been prepared. The terminal amide groups were modified, and the influence of these structural parameters on liquid crystal phases was investigated by polarizing optical microscope (POM) and differential scanning calorimetry (DSC). Three of these new compounds exhibit nematic phase, good thermal stabilities. In general, these liquid crystals with amide as end groups have high melting points and phase transition temperatures, which result from the hydrogen bonds. Based on theoretical calculations, these new molecules with strong electron donating amide as end group have narrower HOMO‐LUMO energy gap and higher dipole moment than tolane.